DEVELOPMENT OF THE COMPETENCIES OF TECHNOLOGY TEACHERS IN THE EDUCATION PROCESS BY APPLYING ACTION RESEARCH - Bankauskiene, Nijole; Masaitytė, Ramunė (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Technology teaching programme has changed over the last decade. It took the path of modernisation. Intensive implementation of information technologies in the technology lessons is underway, the preparation of students for active practical life is being emphasised and the awareness of modern, but healthy daily life is being raised. In this way, new requirements are emerging for the quality of technology teacher activities with regard to their traditional and modern roles in the education process. They need to follow order No. ISAK-54 of 15 January 2007 “On the Approval of the Descriptor of Teacher Professional Competencies”. In their practical work, they must possess, reveal and improve cultural competencies, professional-pedagogical competencies and general competencies. They are in line with the cognitive, functional, personal and ethical competencies of a technology teacher as provided for in the European Qualifications Framework. The article consists of three chapters. The first chapter discusses the activities, functions and roles of technology teachers in contemporary general education school; the content of teacher competencies and its compliance with the competencies of technology teachers provided for in the European Qualifications Framework. The second chapter describes the qualitative method of action research, its content and steps of its implementation. The third chapter summarises the results of a qualitative research carried out in the Lithuanian higher education institution X. The study reviewed the final project reports of current and future technology teachers who were enrolled in a one-year professional study programme from 2007 to 2017. The competencies acquired and developed by the technology teachers through the action research method were indicated. They mostly developed general competencies and professional-pedagogical competencies. Less emphasis was placed on the development of cultural competencies.